Levels of Expression for BMP-7 and Several BMP Antagonists May Play an Integral Role in a Fracture Nonunion: A Pilot Study - Fajardo, Marc (Springer-Verlag, 2009)
Delays in bone healing or even the development of a nonunion could be related to the concentrations and/or functions of the bone morphogenetic proteins (BMPs). The RNA expression profile of the BMPs within fracture nonunion tissue is unknown. This preliminary descriptive study was performed to define the RNA profiles of the BMPs, their receptors, and their inhibitors within human fracture nonunion tissue and correlate them to matched healing bone. All patients had hypertrophic nonunions. Tissue samples taken from the nonunion site of 15 patients undergoing surgical treatment for an established nonunion were analyzed. The RNA expression patterns of BMP-2, BMP-4, BMP-5, BMP-6, BMP-7, BMP-8; BMP receptor Types IA, IB, and II; and the BMP inhibitors chordin, Noggin, Drm (Gremlin), and follistatin were determined in the nonunion (fibrous tissue) and healing bone (callus tissue) using quantitative real-time PCR. Comparison between the nonunion and healing bone samples revealed substantially elevated concentrations of BMP-4, Drm/Gremlin, follistatin, and Noggin in nonunion tissue when compared to healing bone. In contrast, BMP-7 concentration was higher in the healing bone. Our data suggest inhibition of BMP-7, by Drm (Gremlin), follistatin, and Noggin and upregulation of BMP-4 may play an integral role in the development of nonunions.